Development of protective films for enhancing ruminal bypass of micronutrients - Blaine, Kirsty Lana (Kansas State University, 2014)
A series of experiments were conducted in which wheat gluten film forming solutions were modified by various means to produce films that would improve resistance to ruminal degradation. There was an interaction between pH and temperature, whereby low pH (pH 3) and high temperature (75°C) of film forming solution resulted in films that had highest resistance to microbial degradation. Strategies that proved unsuccessful in improving resistance to ruminal degradation included use of the cross-linking enzyme, transglutaminase; induction of a Maillard reaction; and increasing the time of heating film forming solutions. Utilizing HCl versus acetic acid as the means to lower the pH of the film forming solution resulted in poor film formation, which can be attributed to glutenin‟s solubility in acetic acid. When acetic acid was replaced with 25% HCl, however, no compromise in film formation was observed and ruminal degradability was not affected. In order to develop an economical and effective means of encapsulating lysine for rumen bypass, wheat gluten and corn zein were evaluated as encapsulation materials. Coating soybean meal with either wheat gluten or zein resulted in superior protection against ruminal degradation when compared to unprotected soybean meal. Compared to wheat gluten, zein was observed to have greater resistance to ruminal degradation in vitro. Lysine was encapsulated by the spray dry method with wheat gluten or zein. Results from an in vitro ammonia release experiment were inconclusive with respect to effectiveness of the encapsulation process. Wheat gluten films were approximately 59% degraded in pepsin solution. Our results suggest that 72% of the wheat gluten film will bypass the rumen and 59% of the bypass fraction of the film will be degraded in the abomasum. Wheat gluten and zein are suitable candidates for development of encapsulated nutrients for ruminal protection.
Keywords: Wheat gluten; Zein; Lysine; Ruminal degradation; Animal Sciences (0475); Food Science (0359)